Intoxicated or Sober Gnostic? Examining Bāyazīd al-Bisṭāmī and His Controversial Role in Islamic Mysticism - Amir Yousefi; Ali Ashrafimami (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2024)
This article examines Bāyazīd al-Bisṭāmī’s reputation as a mystic of intoxication. In his Kashf al-Maḥjūb, Al-Hujwīrī labelled Bāyazīd as the ‘Pioneer of Intoxicated,’ whereas Ibn ꜤArabī described him as a ‘sober gnostic.’ The central aim of this paper is to determine whether Al-Hujwīrī correctly attributed the ‘Path of Intoxication’ to Bāyazīd or Ibn’ Arabī was justified in praising the accomplishments of Bāyazīd. To explore this issue, this study critically examines Al-Hujwīrī’s writings, employing an analytical-descriptive approach to classical texts on Islamic mysticism, in view of the opinions of modern thinkers such as Ernst and Mojaddedi. The study finds that Al-Hujwīrī’s main reason for attributing intoxication to Bāyazīd lies in his ecstatic utterances, meaning that his claim is unjustified. Therefore, his classification of Sufis as either being ‘Intoxicated Sufis’ or ‘Sober Sufis’ seems questionable. This perspective is supported by Ibn Arabī’s positive appraisal of Bāyazīd, whose original teachings are evidence of his sobriety. Contribution: This paper contributes to the study of Islamic mysticism and its underlying concepts. It also explores the origins of the intoxication vs. sobriety debate, illustrating the reason for the emergence of these labels, which were not challenged or critically examined by later generations of scholars.